Does Race and Gender Inequality Impact Income Growth? - Marrero, Gustavo A.; Rodríguez, Juan Gabriel; van der Weide, Roy (World Bank, Washington, DC, 2021)
Using Integrated Public Use Microdata Series–United States micro-census data from 1960 to 2010, this paper examines whether racial and gender income disparities beget inequality by differentially impacting the growth prospects of the poor, the middle class, and the rich. Racial and gender inequality is found to be bad for income growth of the poor, but not for that of the rich. An investigation into the channels of this effect suggests that higher racial and gender inequality is associated with lower human capital accumulation among the poor and a reduction in the quality of their jobs.